Leisure activities of young drug users and non-drug users: association with five personality factors - B. O. Bazyma; O. O. Serdiuk (Bulletin of Kharkiv National University of Internal Affairs)
The article presents the survey data of 4422 Kharkiv students from higher education institutions of III-IV accreditation levels, among whom 8.1 % used drugs during the last year. Using the validated and adapted BFI-10 screening questionnaire for the rapid diagnosis of five personality factors, the association of personality factors with drug use in the 12 months before the study has been established. The analysis of the leisure activities of student youth in Kharkiv shows that it is quite stable. The most common forms of leisure are spending free time on the Internet, going for walks and socialising with friends, studying and doing homework, watching films and TV programmes (including on the Internet), as well as hobbies and interests. Individual sports activities, reading books, going to cafes and restaurants with friends, playing computer games, and working or having a part-time job are of medium prevalence. The least common forms of active recreation were bowling or billiards, attending a sports section, concerts, clubs or discos. Doing homework (r=0.103, p<0.01), watching TV programmes (r=0.083, p<0.01) and playing sports individually (r=0.063, p<0.01) have a negative correlation with drug use. Low values of the big five personality factors “C” – conscientiousness (r=0.063, p<0.01) and work in free time (r=–0.136, p<0.01) – have a positive correlation with drug use.